The Influence of Financial Literacy, Perception of Online Loans, and Consumptive Behavior in the Community of Yogyakarta Province on the Decision to Use Online Loans - Djamsi, Ningsih; Moin, Abdul (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to examine the influence of financial literacy, perceptions of online loans, and consumptive behavior on the decision to use online loans. Design/methodology/approach: This quantitative study targets the Yogyakarta Province community. Since the population size is unknown, purposive sampling, a non-probability method, was used to select respondents based on these criteria: 1) residing in Yogyakarta, 2) aged 17-35, 3) holding a high school diploma or equivalent, and 4) receiving a monthly income or allowance. The sample size, initially set at 96 using the Lemoshow formula, was adjusted to 150 to meet the minimum requirement for SEM-PLS analysis. Research Findings: The analysis shows that financial literacy, consumptive behavior, and perceptions of online loans have a positive and significant impact on the decision to use online loans. To address these findings, the public should enhance financial literacy to improve financial management and minimize reliance on online loans. Theoretical Contribution/Originality: The study underscores the importance for digital lenders to enhance trust, simplify usability, and offer clear value to attract more consumers. These insights provide valuable guidance for industry stakeholders aiming to improve adoption by addressing consumer perceptions.